ENU-induced mutation in the DNA-binding domain of KLF3 reveals important roles for KLF3 in cardiovascular development and function in mice. - Lois Kelsey; Ann M Flenniken; Dawei Qu; Alister P W Funnell; Richard Pearson; Yu-Qing Zhou; Irina Voronina; Zorana Berberovic; Geoffrey Wood; Susan Newbigging; Edward S Weiss; Michael Wong; et al. (PLoS Genetics, 2013)
KLF3 is a Krüppel family zinc finger transcription factor with widespread tissue expression and no previously known role in heart development. In a screen for dominant mutations affecting cardiovascular function in N-ethyl-N-nitrosourea (ENU) mutagenized mice, we identified a missense mutation in the Klf3 gene that caused aortic valvular stenosis and partially penetrant perinatal lethality in heterozygotes. All homozygotes died as embryos. In the first of three zinc fingers, a point mutation changed a highly conserved histidine at amino acid 275 to arginine (Klf3(H275R) ). This change impaired binding of the mutant protein to KLF3's canonical DNA binding sequence. Heterozygous Klf3(H275R) mutants that died as neonates had marked biventricular cardiac hypertrophy with diminished cardiac chambers. Adult survivors exhibited hypotension, cardiac hypertrophy with enlarged cardiac chambers, and aortic valvular stenosis. A dominant negative effect on protein function was inferred by the similarity in phenotype between heterozygous Klf3(H275R) mutants and homozygous Klf3 null mice. However, the existence of divergent traits suggested the involvement of additional interactions. We conclude that KLF3 plays diverse and important roles in cardiovascular development and function in mice, and that amino acid 275 is critical for normal KLF3 protein function. Future exploration of the KLF3 pathway provides a new avenue for investigating causative factors contributing to cardiovascular disorders in humans.